Effect Of Service Quality On Consumer Loyalty With Consumer Satisfaction As An Intervening Variable At PT. Capella Dinamik Nusantara (Capella Honda 88 Workshop) Pekanbaru - Zahroni, Radifan Zaidan; Sutrisna, Endang (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to determine the influence of service quality on consumer loyalty with consumer satisfaction as an intervening variable at PT. Capella Dinamik Nusantara (Capella Honda 88 Workshop) Pekanbaru. Methodology: In this study, a purposive sampling technique was used to sample 100 respondents. The method used was descriptive statistics with a quantitative approach. Measurement models, structural models, and hypothesis testing with SmartPLS4 software analyze data with a Likert scale. Results: the results show that service quality has a significant direct effect on consumer loyalty with a T-statistic of 2.388>1.96 and a p-value of 0.017<0.05 Service quality significantly affects consumer satisfaction directly with a T-statistic of 13.812>1.96 and a p-value of 0.000<0.05. Consumer satisfaction significantly affects consumer loyalty directly with a T-statistic of 4.740>1.96. and the p-value 0.000<0.05. Consumer satisfaction mediates the effect of service quality on consumer loyalty, which has a significant influence with a T-statistic of 4.627>1.96 and a p-value of 0.000<0.05.. Findings: In this study, consumer satisfaction is able to mediate the influence of service quality on consumer loyalty has a significant influence. Novelty: This study uses a data processing application that is different from the previous research, namely using SmartPLS4. Using different dimensions compared to previous research. Originality: This study provides insight into the influence of service quality on consumer loyalty with consumer satisfaction at PT. Capella Dinamik Nusantara (Capella Honda 88 Workshop) Pekanbaru. The researcher directly distributed the questionnaire to the respondents. Conclusion: With consumer satisfaction obtained from the service quality is able to increase consumer loyalty. Type of Paper: A Research paper.